Economics of conversion from flood to pivot - Selley, Roger, author (Colorado State University. Libraries, 1998)
A number of factors generate producer interest in changing or modifying their irrigation systems. In addition to continual pressure to reduce costs, producers are increasingly facing concerns to reduce water use and the associated leaching of nitrogen. Also, a desire to increase operator output and convenience are often major considerations when looking at alternatives. The availability of funds to invest in system changes and the failure of system components can also prompt a look at the alternatives. The purpose of the discussion here is to focus upon the budgeting of continued operation of a flood irrigation system versus switching to a pivot. The effect upon labor demands will be considered although evaluating the impact of switching to pivots upon potential size of farm and family income is beyond the scope of this paper.
Not digitized by CSUL Digital Services.
Presented at the Central Plains irrigation short course and exposition on February 17-18, 1998 at the Camino Inn in North Platte, Nebraska.